1988
DOI: 10.1038/ki.1988.127
|View full text |Cite
|
Sign up to set email alerts
|

Controlled plasma exchange trial in acute renal failure due to multiple myeloma

Abstract: We studied 29 patients affected by acute renal failure due to multiple myeloma with Bence-Jones proteinuria greater than 1 g/day to evaluate the effectiveness of plasma exchange in the treatment of severe myeloma nephropathy. Renal failure was severe enough to require dialysis in 24 cases, while the remaining 5 patients showed serum creatinine levels greater than 5 mg/dl. The patients were randomly allocated to Group I (15 patients undergoing plasma exchange together with corticosteroids, cytotoxic drug, hemod… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
134
0
5

Year Published

2008
2008
2021
2021

Publication Types

Select...
5
4

Relationship

0
9

Authors

Journals

citations
Cited by 204 publications
(141 citation statements)
references
References 17 publications
2
134
0
5
Order By: Relevance
“…These differences are important to keep in mind when designing clinical trials in which renal outcomes are the endpoints. This may explain why different trials in ARF in myeloma patients produced different results (14)(15)(16)(17)(18).…”
Section: Introductionmentioning
confidence: 96%
“…These differences are important to keep in mind when designing clinical trials in which renal outcomes are the endpoints. This may explain why different trials in ARF in myeloma patients produced different results (14)(15)(16)(17)(18).…”
Section: Introductionmentioning
confidence: 96%
“…A rapid removal of nephrotoxic light chains with plasma exchange, in combination with antimyeloma therapy, could prevent irreversible renal failure by avoiding further renal damage. Two studies suggested that plasma exchange was of benefit; 43,44 however, a prospective comparison of forced diuresis and chemotherapy (10 patients) versus forced diuresis, chemotherapy and plasma exchange (11 patients) found only a trend in favor of the plasma exchange group. 45 On the other hand, a large randomized trial showed no conclusive evidence that plasma exchange improved the outcome in patients with MM and acute renal failure.…”
Section: Supportive Carementioning
confidence: 99%
“…Nonetheless, the clinical benefit of TPE remains controversial. A frequently cited study from 1988 concluded that TPE achieved removal of large amounts of Bence Jones proteins and, in conjunction with chemotherapy, improved kidney function and long-term survival (35). Bence Jones proteinuria significantly decreased.…”
Section: Myeloma Cast Nephropathymentioning
confidence: 99%
“…Although light chains lack criteria for target molecules effectively removed by TPE (e.g., large molecular weight, intravascular location, low rate of turnover), TPE is the most efficient available way to rapidly remove large amounts of light chains (35). TPE, by removing circulating light chains, reduces their filtered load, potentially diminishing renal injury.…”
Section: Myeloma Cast Nephropathymentioning
confidence: 99%